Synthesis of Aqueous Au Core−Ag Shell Nanoparticles Using Tyrosine as a pH-Dependent Reducing Agent and Assembling Phase-Transferred Silver Nanoparticles at the Air−Water Interface - Selvakannan, PR; Swami, Anita; Srisathiyanarayanan, D; Shirude, Pravin S; Pasricha, Renu; Mandale, Anandrao B; Sastry, Murali (Langmuir, 2004)
We demonstrate that the amino acid tyrosine is an excellent reducing agent under alkaline conditions and may be used to reduce Ag+ ions to synthesize stable silver nanoparticles in water. The tyrosine-reduced silver nanoparticles may be separated out as a powder that is readily redispersible in water. The silver ion reduction at high pH occurs due to ionization of the phenolic group in tyrosine that is then capable of reducing Ag+ ions and is in turn converted to a semi-quinone structure. These silver nanoparticles can easily be transferred to chloroform containing the cationic surfactant octadecylamine by an electrostatic complexation process. The now hydrophobic silver nanoparticles may be spread on the surface of water and assembled into highly ordered, linear superstructures that could be transferred as multilayers onto suitable supports by the versatile Langmuir−Blodgett technique. Further, tyrosine molecules bound to the surface of Au nanoparticles through amine groups in the amino acid may be used to selectively reduce silver ions at high pH on the surface of the Au nanoparticles, thus leading to a simple strategy for realizing phase-pure Au core−Ag shell nanostructures.